Inhibition of GABAergic Neurotransmission by HIV-1 Tat and Opioid Treatment in the Striatum Involves μ-Opioid Receptors - Xu, Changqing; Fitting, Sylvia (Frontiers in Neuroscience, 2016)
Due to combined antiretroviral therapy (cART), human immunodeficiency virus type 1 (HIV-1) is considered a chronic disease with high prevalence of mild forms of neurocognitive impairments, also referred to as HIV-associated neurocognitive disorders (HAND). Although opiate drug use can exacerbate HIV-1 Tat-induced neuronal damage, it remains unknown how and to what extent opioids interact with Tat on the GABAergic system. We conducted whole-cell recordings in mouse striatal slices and examined the effects of HIV-1 Tat in the presence and absence of morphine (1 μM) and damgo (1 μM) on GABAergic neurotransmission. Results indicated a decrease in the frequency and amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs) and miniature IPSCs (mIPSCs) by Tat (5 – 50 nM) in a concentration-dependent manner. The significant Tat-induced decrease in IPSCs was abolished when removing extracellular and/or intracellular calcium. Treatment with morphine or damgo alone significantly decreased the frequency, but not amplitude of IPSCs. Interestingly, morphine but not damgo indicated an additional downregulation of the mean frequency of mIPSCs in combination with Tat. Pretreatment with naloxone (1 μM) and CTAP (1 μM) prevented the Tat-induced decrease in sIPSCs frequency but only naloxone prevented the combined Tat and morphine effect on mIPSCs frequency. Results indicate a Tat- or opioid-induced decrease in GABAergic neurotransmission via µ-opioid receptors with combined Tat and morphine effects involving additional opioid receptor-related mechanisms. Exploring the interactions between Tat and opioids on the GABAergic system may help to guide future research on HAND in the context of opiate drug use.